Pneumorrhachis Secondary to a Sacral Decubitus Ulcer - Siamak Moayedi; Lisa Babin (Western Journal of Emergency Medicine, 2016)
An elderly woman with a chronic decubitus sacral ulcer presented to the emergency department with sepsis. A computed tomography of her abdomen showed diffuse gas extending throughout the thoracolumbar spinal canal. Pneumorrhachis is a rare radiographic finding defined as gas within the spinal canal. There are many causes of pneumorrhachis ranging from trauma to infection. In this case the pneumorrhachis was caused by direct spread of gas-forming organisms from vertebral osteomyelitis. Emergency physicians should know about the implication of gas in the spinal canal in the setting of sepsis. [West J Emerg Med. 2016;17(4):466-468.]